Are cognitive functions associated with depression and self-efficacy in stroke patients? - Janavičiūtė , J.; Šinkariova , L. (Neurologijos seminarai, 2020)
Background. Stroke is a common cause of death worldwide. Post stroke cognitive impairment and depression increase mortality rates and complicate recovery. It is not clear why some patients experience post stroke depression and cognitive impairment and others do not. Meanwhile, higher self-efficacy is associated with lower depression, better quality of life, and daily functioning in a sample of stroke patients, so it is important to examine the links between these three phenomena.The aim of the study was to investigate the relationships between cognitive function, depression, and self-efficacy in stroke patients.Materials and methods. The subjects were asked socio-demographic questions. Cognitive function in stroke patients was measured using Addenbrooke’s Cognitive Examination III. The Patient Health Questionnaire was used to measure depression, and The Stroke Self-Efficacy Questionnaire was used for self-efficacy. Finger tapping test was used in the study to determine the location of the stroke.Results and conclusions. The results of the study reveal that cognitive function in stroke patients is not associated with depression or self-efficacy in the general group of stroke patients. In the group of stroke patients with better cognitive function, better attentional function is associated with lower depression and higher self-efficacy. In the same group, poorer language functions are associated with higher scores on the self-efficacy activity subscale and overall self-efficacy scale results. As well as, better spatial abilities are associated with higher scores on the self-efficacy self-management subscale and overall self-efficacy scale results. In the group of stroke patients with poorer cognitive function, better spatial ability is associated with higher self-efficacy.
Keywords: stroke patients; cognitive function; self-efficacy; depression